2012
DOI: 10.1097/ico.0b013e31824d0e22
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Corneal Sensitivity in Patients With Rheumatoid Arthritis

Abstract: Corneal sensitivity was reduced in RA patients but failed to show any association with the subjective symptoms and objective signs of dry eyes. We could assume that reduced corneal sensitivity does not represent a sign of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
8
1
1
Order By: Relevance
“…studies have not found statistically significant correlations between the OSDI score and corneal or conjunctival sensitivity, and the reported correlations are not consistently positive or negative. 19,24,32 One study 33 did report a significant negative correlation; however, the esthesiometer used and the areas of the ocular surface tested were different from those of this study. A study by Golebiowski et al 26 found that as lid margin sensitivity reduced, the meibomian gland dysfunction score increased.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…studies have not found statistically significant correlations between the OSDI score and corneal or conjunctival sensitivity, and the reported correlations are not consistently positive or negative. 19,24,32 One study 33 did report a significant negative correlation; however, the esthesiometer used and the areas of the ocular surface tested were different from those of this study. A study by Golebiowski et al 26 found that as lid margin sensitivity reduced, the meibomian gland dysfunction score increased.…”
Section: Discussioncontrasting
confidence: 73%
“…Some studies show a statistically significant correlation, 24,33 whereas others do not. 19,34 Even the correlation direction is not consistent. Two studies, which used Cochet-Bonnet esthesiometers, showed that as sensitivity decreases, tear breakup times decrease.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations